Soil solarization for controlling soil-borne pathogens in vegetable crops - RAJ, HARENDER; BHARDWAJ, M L (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1995-98 at Jachh to find out the effect of transparent polyethylene mulch on soiltemperature, incidence of soilborne diseases, plant growth and yield of vegetable crops, Solar heating with transparentpolyethylene mulch of a infected field in slimmer for 40 days under irrigated conditions reduced the incidence of soilbornediseases. Mulching with transparent polyethylene resulted in 14°C higher temperature at 8 em soil depth with an averagemaximum temperature of 50° C which was found lethal to soilborne pathogens. Incidence of different soil-borne diseasesin solarized plots ranged between 0 and 6 % in different crops in comparison to 10-21 % in unsolarized plots.